Ultrasound Backscatter Microscopy Image-Guided Intraventricular Gene Delivery at Murine Embryonic Age 9.5 and 10.5 Produces Distinct Transgene Expression Patterns at the Adult Stage - Jiwon Jang; Jyhyun Ahn; Nayeon Lee; Seong-Tae Kim; Dae-Hyuk Kweon; Jae Youl Cho; Kye Won Park; Sunyoung Kim; Keejung Yoon (Molecular Imaging)
In utero injection of a retroviral vector into the embryonic telencephalon aided by ultrasound backscatter microscopy permits introduction of a gene of interest at an early stage of development. In this study, we compared the tissue distribution of gene expression in adult mice injected with retroviral vectors at different embryonic ages in utero. Following ultrasound image-guided gene delivery (UIGD) into the embryonic telencephalon, adult mice were subjected to whole-body luciferase imaging and immunohistochemical analysis at 6 weeks and 1 year postinjection. Luciferase activity was observed in a wide range of tissues in animals injected at embryonic age 9.5 (E9.5), whereas animals injected at E10.5 showed brain-localized reporter gene expression. These results suggest that mouse embryonic brain creates a closed and impermeable structure around E10. Therefore, by injecting a transgene before or after E10, transgene expression can be manipulated to be local or systemic. Our results also provide information that widens the applicability of UIGD beyond neuroscience studies.